Retrospective Evaluation of Pediatric Patients with Extremity Pains - Sezin Naiboğlu; Emrah Naiboğlu; Özden Aksu Sayman; Fatma Gül Demirkan (Bagcilar Medical Bulletin, 2020)

(untitled)
Objective:Recurrent lower extremity pains (growing pains) are the most common non-inflammatory cause of musculoskeletal pain in children. This study aims to investigate musculoskeletal symptoms that may be associated with vitamin D deficiency. We retrospectively examined the data of the patients who applied to the pediatric outpatient clinic and who had vitamin D levels measurement results.Method:We retrospectively evaluated the clinical, laboratory, and diagnostic findings of patients aged 3-16 years, who presented to our outpatient clinic with growing pains between January 2019 and December 2019. We excluded patients with chronic diseases, those with joint findings that might be associated with rheumatological or orthopedic diseases, and those who used vitamin D supplements.Results:There were a total of 103 subjects. Forty-eight subjects were female (46.6%) and 55 (53.4%) were male. The mean age of the subjects was 8.8±4.2 years (3-16). The mean serum 25-hydroxyvitamin D [25(OH) D] level of the subjects was 15.4±6.5 nmol/L. The subjects were categorized according to their 25(OH) D levels. Ten subjects (9.7%) had severe vitamin D deficiency, 25 (23.4%) had vitamin D deficiency, and 42 (40.8%) had vitamin D insufficiency.Conclusion:Leg pains are common in children, and growing pains are the most common non-inflammatory causes of muscle-joint pain in children. Patients with musculoskeletal pain should be screened for vitamin D deficiency. In this study, we aimed to emphasize the importance of vitamin D level assessment in patients presenting with joint-muscle pains that were primarily evaluated as growing pains.